THE QUALITY OF IT PROJECT MANAGEMENT: THE BUSINESS PROCESS AND THE GO PROJECT LEAN APPLICATION - Dewi Nusraningrum; Jaswati Jaswati; Hakiman Thamrin (Manajemen Bisnis, 2020)
This study is analyzing dominant aspects that affect the quality of software-based project development from the point of view of project management. The purpose of this study is to determine the effect of the business process and Go Project Lean (GPL) application on the quality of information technology project management. The research using a quantitative approach by conducting a survey as the research technique. Questionnaires were using the Likert Scale and developed based on the indicators of variables. The population of this study is the users of the GPL application which are the Sales Division, Project Management Office Division, and Application Development Division of PT. Infomedia Nusantara. Data were analyzed using multiple linear regression method and the hypothesis tested using the T-test. The results showed that the influence of business process and GPL Application is very strong and significant to the quality of IT project management. The implication of these findings caused by one of the dimensions which are no investment feasibility analysis calculation application that affects on-time delivery.